Answer:
6: 12
7: 14
8: 16
Step-by-step explanation:
You do the last (y) term given [18] minus the first (y) term [10] given divided by how many terms it takes to get from the last (y) term given minus the first (y) term given [4]. So the equation looks like this:
(18 - 10)/4= 8/4 = 2
First subtract y from both sides to isolate the variable.
25 = 2y-2
Next, add 2 to both sides.
27 = 2y
Last, divide by 2.
13.5 = y
Answer:
yeshjjiih horticulture function finding fog
Answer:
the first one should be -548
Step-by-step explanation:
plug in the values and you should get -30+7(-72-2).
Answer:
9
<u><em>Step-by-step explanation:</em></u>
![\sqrt{15^{2}-12^{2} }](https://tex.z-dn.net/?f=%5Csqrt%7B15%5E%7B2%7D-12%5E%7B2%7D%20%20%7D)
<u><em>Evaluate the equation/expression:</em></u>
9
<u><em /></u>
<em>I hope this helps you</em>
<em>:)</em>